2022
DOI: 10.3390/jof8080806
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Diaporthe Associated with Morinda officinalis in China

Abstract: Diaporthe species are endophytes, pathogens, and saprobes with a wide host range worldwide. However, little is known about endophytic Diaporthe species associated with Morinda officinalis. In the present study, 48 endophytic Diaporthe isolates were obtained from cultivated M. officinalis in Deqing, Guangdong Province, China. The nuclear ribosomal internal transcribed spacer (ITS), partial sequences of translation elongation factor 1-α (tef1-α), partial calmodulin (cal), histone H3 (his), and Beta-tubulin (β-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Aside from the phenotypic traits, phylogenetic and PHI analyses based on the combined sequence datasets of ITS, tef1-α , tub2 , cal , and his3 were successfully applied to justify the novel species. In particular, tub2 , cal , and his3 have a high discrimination power for distinguishing species in Diaporthe , and this is consistent with the results from other studies [ 15 , 18 , 22 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Aside from the phenotypic traits, phylogenetic and PHI analyses based on the combined sequence datasets of ITS, tef1-α , tub2 , cal , and his3 were successfully applied to justify the novel species. In particular, tub2 , cal , and his3 have a high discrimination power for distinguishing species in Diaporthe , and this is consistent with the results from other studies [ 15 , 18 , 22 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…The PHI test result also showed that D. zhaoqingensis and D. chiangmaiensis were not conspecific, indicating that they are different species ( Figure 2 e). Diaporthe zhaoqingensis was isolated as an endophyte on Morinda officinalis [ 18 ], and D. chiangmaiensis was isolated from Magnolia lilifera as an endophyte and saprobe [ 47 ]. However, the morphological characteristics of these two species could not be compared as only gamma conidia were observed in D. zhaoqingensis while alpha conidia were observed in D. chiangmaiensis [ 18 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2−4 It is estimated that approximately one million endophytic fungi are present in various ecosystems. 5 Among them, the genus Diaporthe belongs to the family Diaporthaceae, order Diaporthales, class Sordariomycetes, 6 which has broad host ranges and occurs on many plant hosts, including cultivated crops, trees, and ornamentals. 7−9 Based on morphological and phylogenetic analysis, it consists of approximately 800 species.…”
mentioning
confidence: 99%
“…Endophytic fungi, inhabiting the living tissues of plants without posing any harmful or deleterious symptoms, are a valuable source of functional biomolecules. It is estimated that approximately one million endophytic fungi are present in various ecosystems . Among them, the genus Diaporthe belongs to the family Diaporthaceae, order Diaporthales, class Sordariomycetes, which has broad host ranges and occurs on many plant hosts, including cultivated crops, trees, and ornamentals. Based on morphological and phylogenetic analysis, it consists of approximately 800 species. , To date, approximately 150 secondary metabolites have been obtained from the genus Diaporthe , , encompassing polyketides, terpenoids, alkaloids, macrolides, and steroids. Those compounds exhibit a wide range of bioactivities, including cytotoxic, , antibacterial, , antioxidant, anti-inflammatory, , and enzyme inhibitory effects.…”
mentioning
confidence: 99%